2018
DOI: 10.2337/cd17-0064
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Insulin Degludec/Liraglutide (IDegLira) and Insulin Glargine U100/Lixisenatide (iGlarLixi), Two Novel Co-Formulations of a Basal Insulin and a Glucagon-Like Peptide-1 Receptor Agonist, in Patients With Diabetes Not Adequately Controlled on Oral Antidiabetic Medications

Abstract: Novel co-formulations of basal insulin analogs and glucagon-like peptide-1 (GLP-1) receptor agonists have provided new options for patients with type 2 diabetes who are not reaching recommended glycemic targets. The components of currently available co-formulations (insulin degludec/ liraglutide [IDegLira,] and insulin glargine U100/lixisenatide [iGlarLixi]) act synergistically to address multiple pathophysiologic defects while minimizing the side effects associated with either component when used alone. In Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
2
7
0
3
Order By: Relevance
“…Treatment effect on body weight was consistent with previous findings, a review of which may be found in Wysham et al 2018 and Aroda et al 2018, and demonstrates that the benefits of IDegLira extend beyond glycaemic control. The initial weight loss observed in both treatment groups may be the result of the decrease in insulin dose from pre‐trial doses of approximately 28 U to starting doses of 10 dose steps/U, or up to 16 dose steps/U in some cases .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Treatment effect on body weight was consistent with previous findings, a review of which may be found in Wysham et al 2018 and Aroda et al 2018, and demonstrates that the benefits of IDegLira extend beyond glycaemic control. The initial weight loss observed in both treatment groups may be the result of the decrease in insulin dose from pre‐trial doses of approximately 28 U to starting doses of 10 dose steps/U, or up to 16 dose steps/U in some cases .…”
Section: Discussionsupporting
confidence: 89%
“…Despite this, the rates of severe or BG-confirmed hypoglycaemia were similar between groups. The difference in HbA1c levels observed with IDegLira was achieved at a significantly lower insulin dose than the dose of degludec, supporting a clinically significant contribution of the liraglutide component to overall glycaemic control.Treatment effect on body weight was consistent with previous findings,[15][16][17][18][19] a review of which may be found inWysham et al 2018 andAroda et al 2018, 20,21 and demonstrates that the benefits of IDegLira extend beyond glycaemic control. The initial weight loss observed in both treatment groups may be the result of the decrease in insulin dose from pre-trial doses of approximately 28 U to starting doses of 10 dose steps/U, or up to 16 dose steps/U in some cases 22.…”
supporting
confidence: 89%
“…Therefore, timely addition of insulin should be considered to protect pancreatic β-cells from gluco-lipotoxicity and exploit anabolic effects on musculature. As a consequence, flexible fixed ratio combinations of insulins with a GLP-1RA have been developed: insulin glargine/lixisenatide (iGlarLixi [ 134 ]) and insulin degludec/liraglutide (iDegLira [ 135 ]). With these fixed-ratio combinations, pen applications that require only one injection per day have been provided.…”
Section: Combinations With Sglt2 Inhibitors and Glp-1 Receptor Agonismentioning
confidence: 99%
“…In LixiLan-L and LixiLan-O, iGlarLixi has shown superior reductions in HbA1c relative to its individual components, and in LixiLan-G has also proven to be a useful and more effective therapy in patients failing on GLP-1 RA [12]. Furthermore, post-hoc analyses, systematic reviews, meta-analyses and real-world studies confirmed the feasibility, efficacy and safety of iGlarLixi in treatment of patients with T2DM [18,29,31,32,34,35,40,41,43,44,47,56]. The results obtained with iGlarLixi were achieved regardless of diabetes duration, even in patients with T2DM for >15 years, and its benefits are likely to occur independently of the integrity of beta-cell function [33,35].…”
Section: Discussionmentioning
confidence: 84%
“…Randomized controlled clinical studies were carried out to assess the efficacy and safety of iGlarLixi [31].…”
Section: 2mentioning
confidence: 99%